2018
DOI: 10.1097/01.aoa.0000542350.56459.ef
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prepregnancy Body Mass Index and Severe Maternal Morbidity

Abstract: (JAMA 2017;318(18):1777–1786) Overweight and obesity are associated with increased risks of adverse maternal and neonatal events such as preterm birth, stillbirth, and neonatal or infant death; underweight is also associated with adverse outcomes. However, it is unclear if the risk of severe maternal morbidity increases as body mass index (BMI) increases. This study aimed to determine the association between prepregnancy BMI and severe maternal morbidity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…We found no association between obesity and severe PPH. Previous results on the association between the association between obesity and PPH have been mixed, although our results are similar to the recent findings by Lisonkova et al in a large population‐based sample.…”
Section: Commentsupporting
confidence: 91%
See 2 more Smart Citations
“…We found no association between obesity and severe PPH. Previous results on the association between the association between obesity and PPH have been mixed, although our results are similar to the recent findings by Lisonkova et al in a large population‐based sample.…”
Section: Commentsupporting
confidence: 91%
“…A Dutch case‐control study of 4561 low‐risk pregnant women found a dose‐response relationship between overweight, obesity, and morbid obesity and composite SMM outcome . A population‐based cohort of 743 630 women in the United States similarly found a dose‐response relationship between elevated BMI and composite SMM . A population register‐based study of 292 253 singleton births in Finland also reported an increased risk of composite SMM among obese women .…”
Section: Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…A multiple imputation technique was used to recover the missing values assuming that data were missing at random—which may or may not be true. Of note, an even higher proportion of records with missing BMI data (9%) was reported in a recent related analysis, but carefully addressed through a sensitivity analysis that demonstrated no effect on the main associations of interest.…”
mentioning
confidence: 98%
“…The authors nested a case‐control analysis into a population‐based prospective study in France (EPIMOMS) specifically designed to examine SMM in six regions of the country. By comparison, other recent studies exploring the same associations employed administrative data, such as hospital discharge or health registry data . Cases were all women from a source population of over 180 000 pregnant women (ie, about one‐fifth of deliveries in France and thought to be nationally representative) who developed SMM .…”
mentioning
confidence: 99%